A Qualitative Inquiry into Marketing Strategies in Increasing Student Enrollment: Mind-Share Marketing Analysis of Latecomer University - Rumalessin, Ummu Artha Tsary; Rokhmat, Muhammad; Vera, Lusi Olis; Alamsyah, Redi (Universitas Negeri Jakarta, 2025)
Background Higher education institutions - particularly latecomer or private university - are under growing pressure to differentiate themselves and attract sufficient enrollment to sustain operations and growth due to the heightened competition, shifting demographics, and changing student expectations in open and digital landscape. Purpose This study seeks to critically examine the role of marketing strategies in enhancing student enrollment at Nahdlatul Ulama University of Yogyakarta, a latecomer university in Indonesia. Design/method/approach The study proposes an integrated marketing framework specifically tailored for higher education, grounded in mind-share marketing management and interpreted to the lens of higher education. This study employs a qualitative methodology, utilizing an ethnographic approach to enable an immersive exploration of the social and cultural dynamics within the research context. Results Contrary to prevailing assumptions in existing literature, this study reveals that Nahdlatul Ulama University (UNU) Yogyakarta does not predominantly employ conventional marketing techniques such as advertisements, posters, or television campaigns, which are commonly adopted by many higher education institutions. Instead, UNU Yogyakarta emphasizes the development of sustained, strategic partnerships with key stakeholders - such as Islamic boarding schools, Nahdlatul Ulama-affiliated secondary schools, governmental agencies, and industry representatives - who hold significant influence over its long-term institutional growth. Contribution/value This marketing approach effectively cultivates customer loyalty, thereby ensuring a stable and potentially increasing student enrollment, particularly for latecomer university or private university.